Differential sensitivity and tolerance of some wheat cultivars to stem rust - AND T.C.M. MENON, V.C. SINHA, SHEODHAN SINGH (Indian Phytopathology, 2002)
Wheat cultivars exhibit considerable difference in the losses due to rust infection. This is possibly due to differential sensitivity of the varieties to the rust infection. Efforts were made to explore the possibility of identifying less sensitive or more tolerant wheat varieties to stem rust. The relation between rust severity, and yield loss was studied by using the regression between per cent AUDPC-X (independent variable) and per cent yield loss Y (dependent variable). A linear regression 'Y' on X' in the form of Y = a + bX was fitted by the methods of least squares for each cultivar separately. Accordingly, the varieties were classified into 3 categories on the basis of their rust sensitivity-highly sensitive, moderately sensitive and least sensitive or tolerant.